A case of A large Mucinous Cystadenoma of the Right Ovary: Mucinous Cystadenoma by U/S - Mokhtar, Elrashed (Medico Research Chronicles, 2021)
A single 22 girl unmarried came to the hospital with her parent suffering from an abdominal distension, lower abdominal and pelvic pain radiating to the right side. In clinical examination the doctor feel a very large abdmino-pelvic mass extending from the symphysis pubis to the xiphoid process of the sternum. Then he requested an abdmino-pelvic ultrasound U/S. After that computerized tomography (CT) with contrast media was done as a further radiological investigation.